Kesulitan Siswa dan Penanggulangan Pembelajaran Jarak Jauh PAI di SMP pada Masa Pandemi Covid-19 - emawati; ihya ulumuddin (JURNAL PENELITIAN KEISLAMAN, 2022)
This study aims to explore various student difficulties and efforts to overcome them in Online Learning process of Islamic Religious Education subjects in junior high schools during the Covid-19 period. The research locus were Junior High School of 2 Mataram and Junior High School of 3 Taliwang, West Nusa Tenggara Province. This type of research is descriptive qualitative with data collection methods including observation, interviews, and documentation. The results showed: first, the learning difficulties of students in the two schools mainly came from learning materials, those are the Qur'an and Islamic history, the constraints of limited facilities and gadget media, and internet network barriers. Second, the attitude of teachers in dealing with student difficulties includes: increasing motivation and giving the data quotas. Besides that, they used various Online Learning platforms